2014
DOI: 10.1071/cp13433
|View full text |Cite
|
Sign up to set email alerts
|

Do lignite-derived organic amendments improve early-stage pasture growth and key soil biological and physicochemical properties?

Abstract: 16Commercial lignite-derived products, sold mainly as humate preparations, are widely 17 promoted as plant growth stimulants leading to higher crop yields. These products are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 54 publications
(22 reference statements)
2
19
0
1
Order By: Relevance
“…For example, Little et al [44] found mostly positive shoot and root growth responses with humic acid addition to two different soils for lucerne but not for ryegrass; microbial biomass increased for ryegrass, but not for lucerne on the high pH soil, but was not associated with plant yield. The Masters thesis of Van Tonder in South Africa also illustrates the inconsistency of humate findings.…”
Section: Inconsistent Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Little et al [44] found mostly positive shoot and root growth responses with humic acid addition to two different soils for lucerne but not for ryegrass; microbial biomass increased for ryegrass, but not for lucerne on the high pH soil, but was not associated with plant yield. The Masters thesis of Van Tonder in South Africa also illustrates the inconsistency of humate findings.…”
Section: Inconsistent Resultsmentioning
confidence: 99%
“…There are few rigorous field studies to show benefit from on-farm humate/humic acid application, and findings are variable and inconsistent [1,3,9,20,39,44]. For example, Little et al [44] found mostly positive shoot and root growth responses with humic acid addition to two different soils for lucerne but not for ryegrass; microbial biomass increased for ryegrass, but not for lucerne on the high pH soil, but was not associated with plant yield.…”
Section: Inconsistent Resultsmentioning
confidence: 99%
See 3 more Smart Citations